Influenza vaccination and healthcare workers: barriers and predisposing factors.: A literature review. - Guillari, Assunta; Polito, Francesco; Pucciarelli, Gianluca; Serra, Nicola; Gargiulo, Gianpaolo; Botti, Stefano; Rea, Teresa; Simeone, Silvio (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work. Influenza is a disease that affects a large part of the world’s population annually, with major health, social and economic impacts. Active immunisation practices have always been recommended to counter influenza, especially for people at risk. The recommendations of major health agencies strongly advise influenza vaccination for all healthcare workers, mostly for those in contact with at-risk or immunocompromised individuals. Yet, the influenza vaccination coverage among healthcare workers remains rather low worldwide. This review explore barriers and the facilitators of health care professional toward influenza’s vaccination. Methods. Narrative review consulting the databases: PubMed, CINAHL by combining keywords health care worker, flu, influenza, vaccination, barrier, resistence, hesitangy, between November 2019 and February 2020 Results. From the 1031 records initially, twenty-two primary studies were included in this narrative review. Our results show that the identified facilitators are: desire for self-protection, protection for loved ones and community. Instead, the barriers to vaccination identified are: fear of contracting influenza from the vaccination itself; not considering themselves at risk; to believing believe that their immune system is capable of managing a trivial disease; disease considered trivial, laziness; false beliefs. Discussion and conclusion. Adherence rate on influenza vaccination among health professionals is quite low. The interventions that make it “complex and traceable” flu vaccination refusal increase adherence to this type of vaccination. The results show that current vaccination campaigns do not increase the rate of adherence by healthcare workers. Identifying the predisposing factors and barriers to such vaccination can help to create, develop and test targeted educational programmes.